LASER DECORATIVE PROCESSING OF CLOTHING MADE OF DENIM FABRIC - Khujayeva Malika Ergash kizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Annotation: This article explores the innovative use of laser technology in the decorative processing of denim fabric, aiming to provide a comprehensive overview of its applications in the fashion industry. The study includes an introduction to laser processing, a literature analysis of existing techniques, a detailed description of methods employed, presentation of results, a discussion on the implications, and concludes with suggestions for further research and application in the field.